SENJAKALA TRADISI KENDURIAN DI DESA GRAJEGAN: PERSPEKTIF FENOMENOLOGI AGAMA - Nilawaty, Azzah (UIN Raden Mas Said Surakarta, 2020)
The study discusses the shift in the Grajegan community in interpreting the kendurianor kondhangan. Nowadays, fewer Grajegan people practice the kenduriantradition compared to decades ago. This paper explainsthe causative factors in the perspective of religious phenomenology. This is a field research which uses participatory observation and interviewto collect the data. The data is analysed using the symbolic interpretationmethod. This research revealsthat there are three factors that cause the decrease of the tradition of kendurian in Grajegan. First, the emerge of some religious groups which prohibit the kenduriantradition. Second, the reluctance of some families to perform the kendurian tradition.. Third, the dependence of the family to the figure of mother. A mother has an important role in the preparation of the feast. If this figure does not exist, the kendurianwhich requires the preparation of certain special foods will not occur.